Developing Sports for Economic Growth and Development in Developing Countries - Emmanuel Acquah-Sam (European Scientific Journal, ESJ, 2021)
Many developing countries still struggle to industrialise to speed up the pace of economic growth and development. Given this, they continue to search for antidotes to the challenges of their underdevelopment. Sports development is touted by many as one of the antidotes to the underdevelopment challenges of developing countries. However, the major challenges developing countries face in recent times are how they can develop sports and how they can adequately harness its benefits for economic growth and development. This paper sought to holistically explore the challenges of sports development in developing nations, the long-term complementary strategies or cardinal pillars of sports development in developing nations, and the benefits of sports development and their effects on economic growth and development of developing nations. This paper employed a narrative overview research approach to arriving at its conclusions. It concludes that sports development hinges on the holistic development of ten long-run complementary strategies or cardinal pillars. In addition, sports development offers eight significant benefits that can help achieve economic growth and development in developing nations. One of the study's main recommendations is that sufficient and sustained levels of all kinds of investment in sports, coupled with strong institutions, good governance, and practical and interrelated policies, are critical for sports development and economic growth and development in developing countries.